The Level of Difficulty and Discrimination Power of the Basic Knowledge and Skills Examination (EXHCOBA). - Eduardo Backhoff Escudero; Norma Larrazolo Reyna; Martín Rosas Morales (Universidad Autónoma de Baja California, 2000)
The Basic Knowledge and Skills Examination (EXHCOBA) is one of the few great-scale examinations in Mexico which has been publishing its psychometric parameters.  In this paper we describe the  item analysis results, regarding the exam's difficulty level and discrimination power.  Results show that most of the items have a medium difficulty and a high discrimination power.  They also reveal that the mathematics items have better discrimination power levels than the ones which belong to social science.